Cathodic polarisation of composite LSCF-SDC IT-SOFC electrode synthesised by one-step microwave self-assisted combustion. Issue 5 (May 2019) - Loureiro, Francisco J.A.; Macedo, Daniel A.; Nascimento, Rubens M.; Cesário, Moisés R.; Grilo, João P.F.; Yaremchenko, Aleksey A.; Fagg, Duncan P.
Abstract: Nano-sized composite La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF)-Ce0.8 Sm0.2 O1.9 (SDC) powder was synthesised by one-step microwave self-assisted combustion synthesis and characterized by X-ray diffraction and transmission electron microscopy. Electrochemical performance of composite LSCF-SDC cathode in contact with Ce0.8 Gd0.2 O1.9 (GDC) solid electrolyte under steady state polarisation was studied employing electrochemical impedance spectroscopy in 3-electrode cell configuration. The evolution of elementary steps of oxygen reduction reaction was analysed under cathodic polarisation in potentiostatic mode (up to −0.8 V) in the temperature range 650–750 °C. The composite LSCF-SDC cathode prepared by one-step microwave combustion route demonstrated a lower overall polarisation resistance when compared to literature reports of similar cathodes produced by other synthesis routes.